The status and conservation of sea turtles in Malaysia. - Chan, E.H. (1990)
Four species of sea turtles, Chetonia mydas, Eretmochelys imbricata, Lepidochelys olivacea and Dermochelys coriacea are confirmed to nest in decreasing order of abundance in Malaysia,while a fifth species, Caretta caretta, a predominantly temperate and subtropical nester has also been reported to nest in small numbers in Sarawak. All five species are listed in the IUCN Red Data Book as endangered. In Malaysia,they are to be considered critically endangered. The decimation of nesting populations is attributed to decades of over-exploitation of the eggs,incidental captures in fishing gear,loss of nesting habitat through beach-front development and ineffectively managed turtle-based tourism,directed through turtle hunting in neighbouring countries,marine pollution and nondegradable marine debris. The conservation of sea turtles has been actively pursued since the 1950's in Terengganu,Sabah ans Sarawak,mainly through the operation of beach hatcheries. However,the continuing declines in turtles number have shown that past action has failed to sustain our sea turtle populations. More dramatic action such as a total ban on the sale and consumption of eggs in Terengganu,and a nation-wide ban on the use of large-mashed gill nets has been taken by concerned authorities lately. The ban on the sale and consumption of eggs must be extended to cover all turtle species on a nation-wide basis. Nesting beaches,offshore internesting habitats and feeding grounds must be identified and designated as critical areas for the protection of sea turtles in Malaysia. Since sea turtles migrate across national boundaries,their protection of sea turtles in Malaysia. Since sea turtles migrate across national boundaries, their protection must extend beyond Malaysian waters. Internation cooperation is essential and must be initiated.